Reassessment of the volume of the Las Aguilas mafic-ultramafic intrusives, San Luis, Argentina, based on an alternative geophysical model - Zaffarana, Claudia Beatriz (2011)
In the Sierra de San Luis, Central Argentina, a belt of small and discontinuous lenses of mafic-ultramafic rocks intrude a polydeformed basement and are thought to be the cause of a local increase of the metamorphic grade from amphibolite to granulite facies conditions. This assumption was especially based on forward modelling of a huge gravity anomaly centered over the Sierra de San Luis, which lead some workers to think that a vast volume of mafic-ultramafic rocks lay in shallow levels. Here, we propose an alternative model to explain this anomaly, in which the mafic-ultramafic intrusion is not the ultimate source. Therefore, there is no need to propose a bigger size than that observed in outcrops for the mafic-ultramafic bodies. The thermal effect of the emplacement of mafic-ultramafic sills and dikes on the host rocks was estimated applying a simple analytical solution (error function) for heating of a semi-infinite half space (the country rocks) in contact with a hotter sheet of finite thickness (the mafic-ultramafic intrusion). Results indicate that the effect of the intrusion of these hot mafic magmas is local, because beyond a few hundred meters from the contact zone temperatures never exceed 600 °C, and a few km from the intrusion they barely increase 50 °C relative to the initial temperature. These results, together with the preservation of primary igneous characteristics (such as rhythmic layering) being overprinted by metamorphic textural changes, indicate that the intrusion occurred before regional deformation. It is suggested that the thermal anomaly in the Pringles Metamorphic Complex could have been mainly caused by factors inherent to their geodynamic setting.